Vowel Leght Differences Before Voiced And Voieceless Constant - Miftahul Jannah; Siti Irna Fadillah; Yani Lubis (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
In most languages, vowels before voiced consonants are longer than before unvoiced consonants. Attempts to explain this difference in vowel length with putative physical or physiological limitations in speech production have been generally unsuccessful. We propose the alternative hypothesis that speech communities deliberately vary vowel length to acoustically enhance the final duration of vowel distinctions. According to the principle of continuous contrast, a long vowel should make a short final interval ofappear even shorter and therefore stronger, while a short vowel should make a long final interval appear longer and stronger. so stronger. Therefore stronger.so deaf To support this auditory hypothesis, we show that for jaba/-/apa/ stimuli that vary in duration of medial occlusion and for square-wave stimuli that temporally mimic these speech stimuli, a longer initial segment evokes a change. reliable in both subjects. Restrictions on category labeling towards longer media slot durations.We also discuss other ways that language communities can use sharp contrasts to enhance phonological distinctiveness.